EDITORIAL - Comité Editorial, FII (1999)
No known today, the relevance of the Industrial Research and generally all aspects of innovative activity in promoting industrial competitiveness of a country. This postulate, which has been handled in the world for some years now and in our country for not less than five, there seems to be "permeate" into daily activity towards effective action within organizations linked to Peruvian innovation process. Neither the producers of goods and services in the country, nor the R & D institutions or universities, etc..